2018
DOI: 10.1038/s41467-018-06224-y
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of TGFβ signalling in microglia results in impaired homeostasis

Abstract: TGFβ1 has been implicated in regulating functional aspects of several distinct immune cell populations including central nervous system (CNS) resident microglia. Activation and priming of microglia have been demonstrated to contribute to the progression of neurodegenerative diseases and, thus, underlie stringent control by endogenous regulatory factors including TGFβ1. Here, we demonstrate that deletion of Tgfbr2 in adult postnatal microglia does neither result in impairment of the microglia-specific gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 57 publications
5
131
5
1
Order By: Relevance
“…Previous studies indicated that TGF signaling played vital roles in maintaining microglia homeostasis (Butovsky et al 2014;Qin et al 2018;Zoller et al 2018). Interestingly, we found both the type-1 and type-2 TGFreceptors, which are highly expressed in homeostatic microglia, were notably downregulated after NG2 glia depletion (Fig.…”
Section: Absence Of Ng2 Glia Impairs the Microglia Tgfsignalingmentioning
confidence: 52%
See 1 more Smart Citation
“…Previous studies indicated that TGF signaling played vital roles in maintaining microglia homeostasis (Butovsky et al 2014;Qin et al 2018;Zoller et al 2018). Interestingly, we found both the type-1 and type-2 TGFreceptors, which are highly expressed in homeostatic microglia, were notably downregulated after NG2 glia depletion (Fig.…”
Section: Absence Of Ng2 Glia Impairs the Microglia Tgfsignalingmentioning
confidence: 52%
“…Disrupting TGF signaling in microglia through conditional removal of TGF receptor 2 in the adult brain resulted in loss of microglia homeostasis and altered microglia response to stimulations (Zoller et al 2018). The action of TGFβ on microglia is highly selective and localized, with little spreading between neighboring cells (Qin et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that TGFβ signaling played vital roles in maintaining microglia homeostasis (Butovsky et al, ; Qin et al, ; Zoller et al, ). Interestingly, we found both the Type‐1 and Type‐2 TGFβ receptors, which are highly expressed in homeostatic microglia, were notably downregulated after NG2 glia depletion (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that TGFβ pathway is important for normal microglia development and suppressed in microglia associated with neurodegenerative diseases (Butovsky et al, ; Krasemann et al, ). Disrupting TGFβ signaling in microglia through conditional removal of TGFβ receptor 2 in the adult brain resulted in loss of microglia homeostasis and altered microglia response to stimulations (Zoller et al, ). The action of TGFβ on microglia is highly selective and localized, with little spreading between neighboring cells (Qin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation